Integration of theoretical and the empirical deformations by KALMAN-Filtering in the North Anatolia Fault Zone - Poyraz, F.; Guelal, E. (COPERNICUS PUBLICATIONS, 2007)
Earthquakes occur in regions with intense seismic activities and cause life and property losses. Predicting earthquakes, identifying deformations and decreasing earthquake effects have been major subjects for scientists, engineers, and authorities. One of the theories used for identifying location changes during an earthquake is the elastic half-space model. Recently, the Global Navigation Satellite System has also been used for the same purpose. In this work, the deformations caused by the earthquake across the Marmara Region on 17 August 1999 are determined by theoretical and empirical methods. The data retrieved from the half elastic-space model and GPS measurements were filtered with the Kalman filter technique. The difference between the half elastic-space model and GPS measurements increases in the area close to the fault zone. The study results showed that the fault line is actually not a line but an area within the earthquake region which can be called a deformation zone. To increase the efficiency of the Kalman filter, differences between the theoretical and empirical models were modeled using the Kriging technique. Using the theoretical model which was calibrated by the Kriging griding, forecast values were retrieved for deformations occurred across the earthquake region after the earthquake.
Keywords: 12 NOVEMBER 1999; TURKEY EARTHQUAKE; IZMIT; DUZCE; SLIP; GPS; Geology; Meteorology & Atmospheric Sciences; Water Resources